Найдите значение выражения 16ab−2(− 4a−b)^2 при a=√11, b=√7.

SashaWest SashaWest    2   01.07.2019 01:20    0

Ответы
Deni11111111 Deni11111111  02.10.2020 16:48
16*\/11*\/7 - 2*(16*11+8*\/11*\/7 + 7) = 16*\/77 - 352 - 16\/77 - 14 = - 352 - 14 = - 366
ПОКАЗАТЬ ОТВЕТЫ
Mahaeva33 Mahaeva33  02.10.2020 16:48
16ab-2(-4a-b) ^{2} =16ab-2((-4a)^{2} -(2*(-4a)*b)+ b^{2} )= \\ =16ab-2(16 a^{2} +8ab+ b^{2} )=16ab-32 a^{2} -16ab-2 b^{2} = \\ =-32 a^{2} -2 b^{2} =-2(16 a^{2} + b^{2} )
При а=√11, b=√7:
-2(16*( \sqrt{11} )^{2} +( \sqrt{7} ) ^{2} )=-2(16*11+7)=-2(176+7)= \\ =-2*183=-366
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика